Andrew Bolt, the Far Right and the First Nations : deconstructing a demagogue - Mickler, Steven (UWA Publishing, 2019)
The rights of First Nations peoples are 'racist', left-wing activists are 'fascists' and immigration has become tantamount to a 'foreign invasion'. These are some of the core concepts found in the daily demagoguery of 'Australia's most read' social and political commentator, Andrew Bolt. They are routinely packaged as being underpinned by patriotism, conservative values and egalitarian principles. Yet, as this book argues, Bolt's commentary frequently resonates with the ideas and sentiments of the Far Right -- ultranationalism, cultural chauvinism and a reactionary hostility to progressive thought. History has taught us that only dreadful things come of these ideas. They stand against democracy, internationalism, all that is worthy in Western civilisation, and the security of Indigenous and non-Indigenous peoples alike.